The out-of-plane behaviour of concrete masonry infills bounded by reinforced concrete frames. (1st April 2019) - Nasiri, Ehsan; Liu, Yi
Highlights: A finite element study of the out-of-plane behaviour of masonry infilled RC frames. A 3D non-linear finite element model was developed. Experimental results of four infilled RC frames were used in model validation. Effect of several geometric parameters on infill strength was described in detail. Abstract: The paper presents results of a finite element (FE) study of several critical geometric parameters on the out-of-plane behaviour of concrete masonry infills bounded by reinforced concrete (RC) frames. The development of FE model adopted a three-dimensional simplified micro-modeling technique considering detailed geometry and behaviour characteristics of concrete and masonry units through Concrete Damaged Plasticity (CDP) method. The surface-based cohesive interaction was incorporated to capture the behaviour and failure mechanisms of mortar joints. A concurrent experimental study was also conducted on four infilled RC frames and the results were used to validate the FE model. The model was shown to be capable of simulating accurately the out-of-plane behaviour and strength as well as capturing the cracking pattern and failure modes of infilled RC frames for different geometric and loading situations. The parameters considered in the FE study included infill aspect ratio, infill slenderness ratio, bounding frame stiffness, frame-to-infill interfacial gap, infill opening size and aspect ratio, and web thickness of masonry blocks. The numerical results showed that the out-of-plane behaviour of infilled RC frames was dependent on these parameters and the correlation between each parameter and its effect on the infill strength was described as appropriate.